The earliest development of the Vilnius Franciscan Church and monastery area - Kaplūnaitė, Irma; Jonaitis, Rytis; Indrulėnaitė-Šimanauskienė, Vida; Veževičienė, Vitalija (Archaeologia Lituana, 2025)
When the German Town (a settlement of Catholic merchants and craftsmen) began to emerge in the western part of the present Old Town of Vilnius in the last decades of the 14th century, the Catholic community relocated to this area. St Nicholas Church was built here before 1387 and it was the first Catholic church in the Old Town, around which the German City was established. However, in addition to this house of worship, there was another in the Catholic part of the city – the Franciscan Church of the Assumption of the Blessed Virgin Maria and a monastery.This monastery is considered to be the oldest one in Vilnius, however, the exact time of its construction, as well as that of the church, has not been determined. Due to the lack of historical sources and precise dates, the construction has been dated by different researchers from the first half of the 14th century to the beginning of the 15th century, i.e., with an error of 100 years. Archaeological investigations in the vicinity of the church and the monastery, which have been carried out since 1993, have provided some new hypotheses concerning the chronology and the earliest nature of human activity in this territory. The most recent excavations took place here in 2023, providing new insights into the development of the area through the discovery of objects and interdisciplinary research (radiocarbon dating, analysis of archaeobotanical remains, architectural research). This paper discusses the chronology and nature of the earliest development of the Franciscan church and monastery area, based on the available historical sources, archaeological and architectural research, including the results of most recent investigations.
Keywords: medieval Vilnius; Franciscans; church; graves; archaeology